URGENSI PERAMPASAN ASET SEBAGAI UPAYA PENGEMBALIAN KERUGIAN NEGARA HASIL TINDAK PIDANA KORUPSI - Syahputra, Rivaldi Hendy; Frans, Mardian Putra (LPPM, Universitas Muhammadiyah Riau, 2025)
This research aims to examine the urgency of an Asset Forfeiture Law for proceeds of corruption in Indonesia. Existing laws, such as the Corruption Criminal Act Law and other criminal statutes, haven't been fully effective in asset forfeiture. This is because current mechanisms limit asset seizure and forfeiture to cases where a criminal conviction has already been issued. This limitation creates an opportunity for proceeds of corruption to be hidden or disposed of while legal processes await a criminal judgment. Therefore, a new Asset Forfeiture Law is needed, adopting asset forfeiture mechanisms known in civil law to enable the total recovery of state losses.